2018
DOI: 10.1111/jdi.12805
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide scan for circulating vascular adhesion protein‐1 levels: MACROD2 as a potential transcriptional regulator of adipogenesis

Abstract: Aims/Introduction: Vascular adhesion protein-1 (VAP-1) is a membrane-bound amine oxidase highly expressed in mature adipocytes and released into the circulation. VAP-1 has been strongly implicated in several pathological processes, including diabetes, inflammation, hypertension, hepatic steatosis and renal diseases, and is an important disease marker and therapeutic target. Here, we aimed to identify the genetic loci for circulating VAP-1 levels. Materials and Methods: We carried out a genomic-wide linkage sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…In the TGA subgroup, SNPs on chromosomes 20 and 8 were identified. The lead SNP (rs150246290) and three variants on chromosome 20, all with genome-wide significance, mapped to the MACROD2 gene ( Figure 2A) implicated in chromosomal instability (26) and transcriptional regulation (27). Two SNPs (rs149890280, rs150246290) are suggested to be possible causal variants (Supplemental Table 1).…”
Section: Association Analysis In Overall Population Of Chd Patients Amentioning
confidence: 99%
“…In the TGA subgroup, SNPs on chromosomes 20 and 8 were identified. The lead SNP (rs150246290) and three variants on chromosome 20, all with genome-wide significance, mapped to the MACROD2 gene ( Figure 2A) implicated in chromosomal instability (26) and transcriptional regulation (27). Two SNPs (rs149890280, rs150246290) are suggested to be possible causal variants (Supplemental Table 1).…”
Section: Association Analysis In Overall Population Of Chd Patients Amentioning
confidence: 99%
“…In another genome-wide association study, MACROD2 was identified as a factor influencing vascular-adhesion protein-1 (VAP-1) levels, which the authors confirmed by knockdown of MACROD2. This leads to lower VAP-1 expression in adipocytes, presumably through the transcriptional regulation of VAP-1 [82]. MACROD2 was also reported to leave the nucleus upon DNA damage, dependent on phosphorylation by ATM [75], whereas TARG1 localises from nucleoli to nuclear sites of damage [14], which both have an unclear functional relevance.…”
Section: Macrodomain-containing Hydrolases: Macrod1 Macrod2 and Targ1mentioning
confidence: 99%
“…The lead SNP (rs150246290) and three variants on chromosome 20, all with genome-wide significance, mapped to the MACROD2 gene ( Figure 2A) implicated in chromosomal instability 25 and transcriptional regulation. 26 Two SNPs (rs149890280, rs150246290) are suggested to be possible causal variants ( Table I in Figure 2B). Given the high levels of linkage disequilibrium between these SNPs, they are indicative of the same association signal in both loci.…”
Section: Association Analysis In Overall Population Of Chd Patients Amentioning
confidence: 99%
“…In the TGA subgroup, four SNPs with genome-wide significance mapped to MACROD2 which has been linked to adipogenesis and hypertension. 26,33 Microdeletions in this gene have been implicated as a cause of chromosomal instability in cancers 34 and de novo deletion of exon 5 causes Kabuki syndrome. 35 Chromosomal imbalance is also frequently seen in CHD patients with different morphologies [36][37][38][39] including TGA 40 but so far the MACROD2 locus was not associated with CHD.…”
Section: Tga and Macrod2mentioning
confidence: 99%